2009
DOI: 10.1111/j.1467-9280.2009.02480.x
|View full text |Cite
|
Sign up to set email alerts
|

Losing Access to the Native Language While Immersed in a Second Language: Evidence for the Role of Inhibition in Second-Language Learning

Abstract: Adults are notoriously poor second-language (L2) learners. A context that enables successful L2 acquisition is language immersion. In this study, we investigated the effects of immersion learning for a group of university students studying abroad in Spain. Our interest was in the effect of immersion on the native language (L1), English. We tested the hypothesis that immersion benefits L2 learning as a result of attenuated influence of the L1. Participants were English-speaking learners of Spanish who were eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
300
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(361 citation statements)
references
References 37 publications
(56 reference statements)
26
300
1
3
Order By: Relevance
“…In addition to the benefits of language transfer identified in the attainment and maintenance of English, exposure to English emerged as a predictor of English proficiency across our overall sample, consistent with previous findings in younger adults 2 (e.g., Marian et al, 2007;Linck et al, 2009) and older adults (Barresi et al, 1998;Nanchen et al, 2017). It is possible that, in learners who cannot engage efficient cognitive control skills to ameliorate interference from other languages, establishment of languagespecific resonance through continued immersion is especially critical in the language acquisition process.…”
Section: Continued Exposure To Englishsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition to the benefits of language transfer identified in the attainment and maintenance of English, exposure to English emerged as a predictor of English proficiency across our overall sample, consistent with previous findings in younger adults 2 (e.g., Marian et al, 2007;Linck et al, 2009) and older adults (Barresi et al, 1998;Nanchen et al, 2017). It is possible that, in learners who cannot engage efficient cognitive control skills to ameliorate interference from other languages, establishment of languagespecific resonance through continued immersion is especially critical in the language acquisition process.…”
Section: Continued Exposure To Englishsupporting
confidence: 78%
“…For example, Barresi et al (1998) found in a longitudinal study that older individuals who reported living in a household with other adults showed better naming performance while those who reported high-passive language exposure through television showed lower performance. In younger bilingual adults and language learners, language exposure has similarly emerged as an important predictor of abilities (e.g., Marian et al, 2007;Linck et al, 2009) and may play an important role in the maintenance of L2 in older adults (e.g., Nanchen et al, 2017). It has been suggested that continued use of a language provides continued activation and strengthens its representations, creating language-specific resonance that boosts the network underlying the novel language and reduces interference from other languages (MacWhinney, 2012).…”
mentioning
confidence: 99%
“…Americans taking a Spanish course in the United States showed lower Spanish proficiency and greater accessibility of English words than a group taking the same course of Spanish in Spain (35). Although the linguistic context outside of class no doubt contributed to the United States group's higher L1 accessibility, the cues in the visual environment may have also mattered: the everyday environment of the United States group was saturated with cues to American culture, which heightened L1 accessibility.…”
Section: Discussionmentioning
confidence: 97%
“…Our results confirm such patterns and insists on the spared comprehension in the host language, as a consequence of long lasting immersion. As mentioned before, long-life L2 exposure has been linked to increased grey matter densities in areas such the inferior parietal lobules (Abutalebi et al, 2015) which are involved in with semantic and phonological (Seghier et al, 2004) and temporo-parietal lesions and whose impairment are associated with comprehension deficit in both acute deficits and degenerative situations (Kreisler et al, 2000). It is thus probable that such used-dependent neural plasticity may correlate with second language preservation in late life.…”
mentioning
confidence: 99%